Investment in Human Capital and Corporate Social Responsibility in SMEs providing accommodation services. The specificity of family firms - Campos-Valenzuela, Marta; Diéguez-Soto, Julio; Ruiz-Palomo, Daniel; López-Marfil, Lidia (My University, 2022)
The general purpose of this paper is to investigate the effect of Human Capital Investment (HCI) on Corporate Social Responsibility (CSR) practices in small and medium-sized enterprises providing accommodation services. Thus, this study has two aims: first, analyzing the effect that HCI exerts on CSR practices; and second, examining the moderating effect of being a family firm on prior relationship. The sample is obtained from a survey carried out during 2017 in Spain to 1136 family and non-family businesses, which 41 belong to "Accommodation Services" and the methodology used is PLS-SEM.
Keywords: Recursos humanos; Responsabilidad social de la empresa; Pequeñas y medianas empresas; Alojamientos turísticos; Human Capital Investment; Corporate Social Responsibility; SMEs; Family firm; Accommodation services